The order effect of combined endurance and strength loadings on force and hormone responses: effects of prolonged training - Schumann, M.; Walker, S.; Izquierdo, M.; Newton, R. U.; Kraemer, W. J.; Häkkinen, K. (European Journal of Applied Physiology, 2014)
Purpose To examine acute responses and recovery of force and serum hormones to combined endurance and strength loadings utilizing different orders of exercises before and after training. Methods Physically active men were matched to an order sequence of endurance followed by strength (E + S, n = 12) or strength followed by endurance (S + E, n = 17). The subjects performed one experimental loading consisting of steady-state cycling and a leg press protocol before and after 24 weeks of order-specific combined training. Results No between-group difference in acute reductions of force was observed at week 0 (E + S -23 %, p < 0.001; S + E -22 %, p < 0.01) and 24 (E + S -25 %, p < 0.001; S + E -27 %, p < 0.001) and recovery in force was completed after 24 h in both groups at week 0 and 24. Concentrations of growth hormone (22-kDa) increased post-acute loading at week 0 (E + S, +57 fold, p < 0.05; S + E, +300 fold, p < 0.001; between-groups p < 0.001) and 24 (E + S, +80 fold, p < 0.01; S + E, +340 fold, p < 0.05; between-groups p < 0.05). No significant acute responses in concentrations of testosterone were observed at week 0 or 24. However, at week 0 testosterone was reduced during recovery following the E + S loading only (24 h -23 %, p < 0.01; 48 h -21 %, p < 0.001; between-groups at 24 and 48 h, p < 0.05), but was no longer observed after training. 1RM strength improved similarly in E + S (13 %, p < 0.001) and S + E (17 %, p < 0.001). Conclusions This study showed an order effect (E + S vs. S + E) in concentrations of testosterone during 2 days of recovery at week 0, which was diminished after 24 weeks of training. The initial difference in testosterone concentrations during recovery did not seem to be associated with strength development.